Recent archaeomagnetic studies in Slovakia: Comparison of methodological approaches - KUBIŠOVÁ, Lenka (Contributions to Geophysics and Geodesy, 2016)
We review the recent archaeomagnetic studies carried out on the territory of Slovakia, focusing on the comparison of methodological approaches, discussing pros and cons of the individual applied methods from the perspective of our experience. The most widely used methods for the determination of intensity and direction of the archaeomegnetic field by demagnetisation of the sample material are the alternating field (AF) demagnetisation and the Thellier double heating method. These methods are used not only for archaeomagnetic studies but also help to solve some geological problems. The two methods were applied to samples collected recently at several sites of Slovakia, where archaeological prospection invoked by earthwork or reconstruction work of developing projects demanded archaeomagnetic dating. Then we discuss advantages and weaknesses of the investigated methods from different perspectives based on several examples and our recent experience.